(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The muturalization and changes of different sorts of grape sprout has been researched in different levels of chill-durability. As research testifies, it turns out, that those changes are accustomed to two breaking periods: l)early spring, 2) late autumn (autumn-winter). The changes and differentiation of grapes’ sprout tissues are appeared in early spring and summer periods. This differentiation is not visible in autumn, if there are favourable conditions.